Party-society relations in the Republic of Cyprus: Political and societal strategies: Giorgos Charalambous and Christophoros Christophorou (eds) New York: Routledge, 2016 pp … - Triga, Vasiliki (My University, 2019)
Although a small nation on the periphery of the Eastern Mediterranean, the island of Cyprus has tended to attract academic interest due to its longstanding problem known as the ‘Cyprus problem’. There is a substantial volume of scholarly works drawing from various fields such as political science, international relations, law, history, sociology, and media studies that focus on the various political and societal dynamics triggered by the Cyprus problem. More recently, Cyprus hit the global headlines at the height of the financial crisis as one of the Eurozone countries that received a bailout from the so-called Troika. Depositors were bailed-in and two of its major banks collapsed (one since rescued) as it became the first Eurozone country to introduce countrywide capital controls-a full two years before Greece did. The impact of the financial crisis has led to further academic interest in the politics of countries afflicted by the tumultuous events. Despite such renewed academic attention, there is to date a limited, systematic literature for the analyst to consult on the politics and society of Cyprus.